Pengaruh kondisi sosial dan manfaat pada minat penggunaan qris bagi mahasiswa Universitas Nurul Jadid - Pradani, Rizki Febri Eka; Widat, Shafwil (Jurnal Pendidikan Ekonomi (JUPE), 2024)
QRIS users in Indonesia have increased every year, which in its implementation is not only applied to traders or MSMEs, but students as consumers can also use QRIS as a payment method, one of which is at Nurul Jadid University. This study aims to determine the effect of social conditions and benefits on interest in using QRIS as a cashless society for Nurul Jadid University students. This type of research uses quantitative research methods with an associative approach. The population in this study were active students of Nurul Jadid University. Determination of the sample using probability sampling technique with 350 respondents. Data collection techniques used observation and questionnaires. This study uses data analysis techniques in the form of validity tests, reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing in the form of t tests and F tests.The results showed that (1) The social condition variable has a positive and partially significant effect on interest in using QRIS thitung (27,128) > ttabel (1,967) signifikan <0,001 . (2) The benefit variable has a partially positive and significant effect on interest in using QRIS thitung (27,128) > ttabel (1,967) signifikan <0,001. (3) Social condition variables and benefits have a positive and significant effect simultaneously on interest in using QRIS Fhitung (550,757) > Ftabel (3,02) signifikan < 0,05.